Indigofera torulosa W. Khan-a New Species from the Deccan Plateau - Wadood Khan, M. A. (Indian Forester, 1982)
Indigofera torulosa Wadood Khan (Fabaceae) is described from beed district. Recent exploration of Marathwada region on the deccan plateau of this country has yielded a rew interesting taxa of the flowering plants. The present report describes one such species of the Fabaceae, collected from the gravelly edges of the U-shaped valley formed around a ran of the Penganga river near Sautada In the district of Beed. The valley harbours a typical dry deciduous forest vegetation while the new taxon occupies open situations on slopes. Following is the description of the taxon together with relevant notes.